2007
DOI: 10.2307/25066606
|View full text |Cite
|
Sign up to set email alerts
|

Shear-Stress Dependence of Dinoflagellate Bioluminescence

Abstract: Fluid flow stimulates bioluminescence in dinoflagellates. However, many aspects of the cellular mechanotransduction are incompletely known. The objective of our study was to formally test the hypothesis that flow-stimulated dinoflagellate bioluminescence is dependent on shear stress, signifying that organisms are responding to the applied fluid force. The dinoflagellate Lingulodinium polyedrum was exposed to steady shear using simple Couette flow in which fluid viscosity was manipulated to alter shear stress. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 53 publications
0
50
0
Order By: Relevance
“…The bioluminescence of dinoflagellates is stimulated by the velocity gradient rather than absolute flow velocity Maldonado and Latz, 2007) and can thus serve as a reporter of local velocity gradients and hydrodynamic stresses, making it a unique tool for both field Rohr et al, 2002) and laboratory (Chen et al, 2003;Stokes et al, 2004) flow visualization. Based on laboratory studies using well-characterized flow fields (Latz et al, 1994;Latz and Rohr, 1999;Latz et al, 2004a;Latz et al, 2004b) a statistical model has recently been developed that predicts bioluminescence intensity as a function of shear stress level and cell concentration (Deane and Stokes, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The bioluminescence of dinoflagellates is stimulated by the velocity gradient rather than absolute flow velocity Maldonado and Latz, 2007) and can thus serve as a reporter of local velocity gradients and hydrodynamic stresses, making it a unique tool for both field Rohr et al, 2002) and laboratory (Chen et al, 2003;Stokes et al, 2004) flow visualization. Based on laboratory studies using well-characterized flow fields (Latz et al, 1994;Latz and Rohr, 1999;Latz et al, 2004a;Latz et al, 2004b) a statistical model has recently been developed that predicts bioluminescence intensity as a function of shear stress level and cell concentration (Deane and Stokes, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…At smaller scales, spermatozoa exhibit rheotaxis, likely resulting from a passive hydrodynamic effect, whereby the combination of a gravitational torque and a shear-induced torque orients the swimming direction preferentially upstream (14)(15)(16). Responses to shear are also observed in copepods and dinoflagellates, which rely on shear detection to attack prey or escape predators (5,(17)(18)(19), orient in flow (20), and retain a preferential depth (21). Evidence of shear-driven motility in prokaryotes is limited to the upstream motion of mycoplasma (22), E. coli (23), and Xylella fastidiosa (24), all of which require the presence of a solid surface.…”
mentioning
confidence: 99%
“…Similar to ciliates, mechanoreceptors that enable predator detection have also been described for dinoflagellates (Maldonado & Latz, 2007). Jakobsen et al (2006) reported highly effective escape behaviour for two different dinoflagellates when being attacked by a predator.…”
Section: Transfer Techniquementioning
confidence: 91%